The - Funder, David Charles
The Personality Puzzle gets students excited about personality psychology, demonstrating that it is relevant to their lives and thus actually fun to explore. Over six editions, author David Funder has established himself as the master of the readable textbook, always conveying the motivations behind psychological inquiry while never skimping on the science